Pollen allergens sensitization characteristics and risk factors among allergy rhinitis of children in mainland China: A multicenter study - Wenting Luo; Yusi Li; Lina Xu; Yongmei Yu; Jinhai Ma; Yu Wang; Yi Wang; Huajie Wu; Meng Xv; Liting Wu; Teng Zhang; Jingping Zheng; et al. (Heliyon, 2023)
Background: No comprehensive multicenter study of sensitization patterns among patients with allergic rhinitis (AR) to various common pollen allergens was available nationwide, and risks factors of pollen-induced allergic rhinitis (PiAR) in mainland China was unclear. This study aimed to fill this gap. Methods: A multicenter study was performed on 736 AR patients aged below 18 from four regions of mainland China. Patients completed a standardized questionnaire asking for the environmental risk factors and AR severity, and undertook skin prick tests (SPT) with 14 common pollen allergens. Findings: Among the 736 patients, 341 patients (46.33%) suffered at least one positive pollen allergen sensitization. The positive rate of pollen allergens was significantly higher in the high-age group (Damato et al., 2007; Wang et al., 2018; Luo et al., 2016; Demoly et al., 2011; Sampson and Albergo, 1984; Li et al., 2009; Luo et al., 2021; Ziska and Beggs, 2011; Melén et al., 2020; Jensen-Jarolim, 2017; Rönmark et al., 2017; Ge et al., 2017) [6-17] than the low-age group ( ≤ 5), while no significant difference was found between the sexes. The sensitizations to pollen allergens varied widely among four geographical areas. The positive rate was higher in north China and west China than in east China, and south China had the lowest positive rate. The region of residence, ages, ethnic minorities, history of pollen exposure, the material of living room floor and material of pillow were statistically significant risks of PiAR. Interpretation: This study provides new insights into the pollen allergens sensitization characteristics in AR and the factors affecting PiAR in mainland China.